Advances in synthesis of biodiesel via enzyme catalysis: Novel and sustainable approaches. (January 2015) - Guldhe, Abhishek; Singh, Bhaskar; Mutanda, Taurai; Permaul, Kugen; Bux, Faizal
Abstract: Biodiesel, a renewable fuel has a great potential in fulfilling an ever-increasing transport fuel demand. The enzymatic conversion process of feedstock oil to biodiesel is greener when compared to the conventional approach of chemical conversion due to mild reaction conditions and less wastewater generation. Lipases obtained from various microbial sources have been widely applied as catalysts for the conversion of oil to biodiesel. Biodiesel and glycerol obtained by enzymatic conversion have shown a higher purity as compared to that obtained by other conversion techniques. Enzymatic conversion of oil to biodiesel is less energy intensive because of milder reaction conditions and fewer purification steps involved in processing. Lipases, due to their catalytic efficiency and specificity, have emerged as a great tool for converting a wide range of feedstock oils to biodiesel. This manuscript presents an overview of the use of enzymatic conversion for making biodiesel production sustainable and environmentally-friendly. The constraints of enzymatic conversion are the high cost of the enzyme and its inhibition by alcohol and glycerol. The possible solutions to overcome these constraints are discussed. Recent advances to develop an effective process for enzymatic conversion of feedstock oils into biodiesel are critically evaluated. Prospective and challenges in scaling up of this technology are also discussed.